Electric field effect on magnetism in metallic ultra-thin films - Chiba, Daichi (Frontiers in Physics, 2015)
Recent experimental developments on the electric field effect on magnetism in metallic magnetic materials are reviewed. The change in the electron density at the surface of metallic ultra-thin magnets by the application of an electric field results in modulations of the Curie temperature, magnetic moment, magnetic anisotropy, and domain wall velocity. The study focused on this paper is the electric field effect on the Curie temperature (magnetic phase transition) in Pt/Co ultra-thin film systems. Electric field modifications of the magnetic moment induced by ferromagnetic proximity effects in Pd, which is usually a nonmagnetic element, are also discussed.